Nabokov's cinematic afterlife - Mazierska, Ewa (McFarland & Company, Inc., Publishers, 2011)
"This work offers critical studies of films that adapted works by Vladimir Nabokov. One of the most screened twentieth century authors (with over 10 books adapted for cinema), his works are full of quirky and forbidden romance, and his writing is renowned for its cinematic qualities. A final chapter compares the similarities between Nabokov and Jean-Luc Godard."--Provided by publisher.